Computer Forensics in Cloud Computing Systems - Pedro Ramos Brandao (Budapest International Research and Critics University, 2019)
The challenges on traditional Computer Forensic mythology in facing with the growing adoption of Cloud Computing services and models by corporations and organizations. We analyse the results of recent research in analysis of computers’ physical memory, new methodologies and tools, and how these technologies can be applied to computer forensics in this specific context.